TARGETING THE SIGMA-1/NMDA RECEPTOR COMPLEX TO AMELIORATE COGNITIVE DEFICITS AND NEGATIVE SYMPTOMS IN SCHIZOPHRENIA - Łukasz Ćmok; Julia Dobrowolska; Justyna Chudy; Jakub Robert Skalski; Gabriela Daniel; Karolina Halat; Antoni Hajdas; Natalia Kaczmarczyk; Iga Kałka; Julia Szmuc (International Journal of Innovative Technologies in Social Science, 2026)
Background: The main limitation of contemporary schizophrenia treatment is the insufficient clinical response of negative symptoms and cognitive deficits to current antipsychotics. In light of the NMDA receptor hypofunction hypothesis, research increasingly targets novel glutamatergic modulators. Aim: This study analyzes the molecular mechanisms linking Sigma-1 receptor (σ1R) dysfunction with glutamate N-methyl-D-aspartate receptor (NMDAR) hypofunction in schizophrenia and assesses the therapeutic potential of σ1R agonists (e.g., fluvoxamine, pridopidine, AF710B) in reducing drug-resistant symptoms. It also examines their broader socioeconomic implications. Methods: A narrative review of the literature was conducted using the PubMed database, primarily focused on publications from 2006 to 2026; however, earlier studies were incorporated if they provided crucial mechanistic insights. European Brain Council reports were also included. Results: Accumulated evidence indicates that σ1R stabilizes NMDAR transport to the cell membrane and modulates its activity. Pharmacological stimulation by σ1R agonists promotes the restoration of synaptic plasticity and cellular homeostasis, effectively eliminating endoplasmic reticulum stress and inflammation. This results in the restoration of dendritic spine structure and a significant improvement in memory, cognitive flexibility, and social interactions. Conclusion: Targeted modulation of the σ1R/NMDAR complex is a highly promising neuropharmacological strategy in schizophrenia management. Augmenting standard treatment with targeted σ1R agonists may effectively address the drug-resistant aspects of schizophrenia pathophysiology, paving the way for a significant improvement in patient functional prognosis.